Review of the shrimp-associated goby genus Lotilia (Actinopterygii: Perciformes: Gobiidae), with description of a new species from the West Pacific - Shibukawa, Koichi; Suzuki, Toshiyuki; Senou, Hiroshi (Zootaxa, 2012)
The Indo-West Pacific gobiid fish genus Lotilia, symbiotically associated with alpheid shrimps, is reviewed. The genus com-prises two species, viz. L. graciliosa Klausewitz, 1960 and L. klausewitzi sp. nov., the latter of which is described herein basedon 11 specimens (including seven type specimens) from Japan, Australia and the Bismark Archipelago. Lotilia klausewitzi, pre-viously misidentified as L. graciliosa in the West Pacific, is readily distinguished from L. graciliosa by having the followingfeatures, in addition to some minor differences in the sensory-papillae configuration on the cheek: cephalic sensory canals andassociated pores present (vs. absent in L. graciliosa); 7+6=13 branched caudal-fin rays (vs. 7+7=14); pale area on dorsum fromsnout to dorsoanterior part of body relatively long, extending posteriorly to, or beyond, base of fifth spine of first dorsal fin (vs.extending posteriorly to around base of third or fourth spine); a faint, relatively small dark grayish brown spot at center of firstdorsal fin behind third or fourth spine, and its paler margin usually absent or obscure (vs. conspicuous ocellated black spot withvivid pale margin at center of first dorsal fin, extending anteriorly beyond third spine); and a submarginal row of black spots oncaudal fin (vs. absent). Geographic records based on the specimens examined and underwater photographs indicate that L. gra-ciliosa appears to be restricted to the Red Sea and its adjacent areas, whereas L. klausewitzi is widely found in the West Pacific. Lotilia is re-diagnosed, and L. graciliosa is re-described based on five specimens including the holotype.